Giant Hypothalamic Hamartoma Treated with Thermocoagulation: A Case Report and Literature Review - Wangsawatwong, Piyanat; Bunyaratavej, Krishnapundha (Thai Journal of Neurological Surgery, 2025)
Hypothalamic hamartomas (HH) is a rare congenital nonneoplastic developmental lesion which often presents with intractable seizure, cognitive impairment, precoccious puberty and delay development. Gelastic seizure is the hallmark and epileptiform discharges are electrographically confirmed to originate within the hamartoma1. Surgical intervention for complete removal or disconnection is typically needed for seizure control. Size and anatomical features of HH play an important role for surgical considerations. Giant hypothalamic hamartomas (GHH) are defined when their dimensions exceed 30 mm2. Most of them are unable to be completely resected. Authors present a case of a 5-year-old girl with intractable gelastic seizure. Magnetic resonance imaging (MRI) of the brain revealed 37 x 27 x 23 mm giant hypothalamic hamartoma. Post stereotactic radiofrequency thermocoagulation, the patient had 90% seizure reduction. Review literature of various surgical interventions of HH is also presented.